2021
DOI: 10.1038/s41385-021-00411-9
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke exposure attenuates the induction of antigen-specific IgA in the murine upper respiratory tract

Abstract: The upper respiratory tract is highly exposed to airborne pathogens and serves as an important inductive site for protective antibody responses, including mucosal IgA and systemic IgG. However, it is currently unknown to what extent inhaled environmental toxins, such as a cigarette smoke, affect the ability to induce antibody-mediated immunity at this site. Using a murine model of intranasal lipopolysaccharide and ovalbumin (LPS/OVA) immunization, we show that cigarette smoke exposure compromises the induction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Variables that can interfere with critical readouts need to be categorically accounted for during clinical testing. In this regard, the studies discussed previously 7 , 9 , 10 provide reasonable evidence that cigarette or e-cigarette use can detrimentally impact IgA-based immunity in the upper airways. At a minimum, their use could introduce variability and skew the interpretation of IgA-related data, and at worst, promote discontinuation of intranasal vaccine candidate trials for which IgA induction is a primary outcome.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Variables that can interfere with critical readouts need to be categorically accounted for during clinical testing. In this regard, the studies discussed previously 7 , 9 , 10 provide reasonable evidence that cigarette or e-cigarette use can detrimentally impact IgA-based immunity in the upper airways. At a minimum, their use could introduce variability and skew the interpretation of IgA-related data, and at worst, promote discontinuation of intranasal vaccine candidate trials for which IgA induction is a primary outcome.…”
mentioning
confidence: 75%
“…Recently, our research groups 9 , 10 showed that cigarette smoke and e-cigarette exposure can interfere with the induction of antigen-specific IgA immunity in the upper airways. In humans, Rebuli and colleagues 9 showed that the induction of influenza-specific IgA was diminished by about 40% in the nasal lavage fluid of smokers and e-cigarette users at day 8 following live-attenuated influenza virus immunisation relative to never-smokers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Gohy and colleagues previously noted increased PIGR expression in the large airways of smokers 40 . Conversely, McGrath and colleagues found that cigarette smoke attenuated pIgR protein expression in vivo in response to challenge with ovalbumin and lipopolysaccharide 48 . Similarly, Rostami and colleagues showed cigarette smoke extract treatment in vitro reduced multiple secretory cell defense genes including PIGR 37 .…”
Section: Discussionmentioning
confidence: 97%
“…Tobacco affects immune status by decreasing immunoglobulin levels, including those of IgA, IgM, and IgG in serum, and IgA in saliva ( 61 , 62 ). Periodontal parameters such as bleeding on probing, probing depth, and attachment loss are also affected.…”
Section: Discussionmentioning
confidence: 99%